Economic Security of Russian Regions: Risk Factors and Consequences of the Covid-19 Pandemic - Zoya P. MEJOKH; Elena V. KOROLYUK; Dzhamiliya A. SOZAEVA; Nadezhda V. PILIPCHUK; Evgeniya K. KARPUNINA (Communications of International Proceedings, 2020)
The purpose of the study is to reveal the impact of the COVID-19 pandemic on the economic security of Russian regions, as well as to determine the appropriate directions for stabilizing the socio-economic situation. The authors identified specific features of the COVID - 19 pandemic that determine the nature of its impact on regional development. The authors structured the economic security of the region in terms of the emergence of risk factors and threats from the COVID-19 pandemic (economic security of the real sector of the economy of the region; economic security of the financial sector of the region; economic security of the social sphere of the region), and also defined a list of economic indicators that characterize each element of economic security. The authors analyzed the dynamics of indicators of economic security of Russian regions during the beginning of the pandemic based on operational data from the Federal state statistics service of the Russian Federation, as well as concluded that the impact of the COVID-19 pandemic on the state of economic security of Russian regions is heterogeneous, certain indicators of economic security at the regional level are decreasing. The authors suggested ways to stabilize the economic security of Russian regions.
Keywords: economic security; region; COVID-19; threats; recession; risk factors; economic security indicators